Pure spinor b-ghost in a super-Maxwell background - Bakhmatov, Ilya [UNESP]; Berkovits, Nathan [UNESP] (Springer Nature, 2013)
In the pure spinor formalism for the superstring, the b-ghost is a composite operator satisfying {Q, b} = T where Q is the pure spinor BRST operator and T is the holomorphic stress tensor. The b-ghost is holomorphic in a flat target-space background, but it is not holomorphic in a generic curved target-space background and instead satisfies ∂̄b = [Q,Ω] for some Ω. In this paper, Ω is explicitly constructed for the case of an open superstring in a super-Maxwell background. © SISSA 2013.
Keywords: BRST Symmetry; Superstrings and Heterotic Strings